137k views
4 votes
Hello, how can I do this equation?


9^x - 3 = 2 * 3^x

Please solve it with all steps and with an explanation.

Thanks!

User Kampu
by
6.5k points

1 Answer

7 votes
(9^x) - 3 = 2*3^x
(9^x) - 3 - (2*3^x) = (2*3^x) - (2*3^x)
(9^x) - (2*3^x) - 3 = 0
(3^2)^x - 2*(3^x) - 3 = 0
3^(2x) - 2*(3^x) - 3 = 0
3^(x*2) - 2*(3^x) - 3 = 0
(3^x)^2 - 2*(3^x) - 3 = 0
z^2 - 2*z - 3 = 0 ............ let z = 3^x
(z - 3)(z + 1) = 0

If z-3 = 0, then z = 3 when we isolate z
If z = 3, and z = 3^x, then
z = 3
3^x = 3
3^x = 3^1
x = 1
which is a solutin in terms of x

If z+1 = 0 then z = -1
If z = -1 and z = 3^x, then there are NO solutions for this part of the equation
The quantity 3^x is never negative no matter what the x value is

---------------------------------------------------------------

Answer: x = 1
User Ricardo Romo
by
6.4k points